2018 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2018
DOI: 10.1109/iros.2018.8594475
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Next Generation of Robotic Waiters

Abstract: In this paper, the problem of suppressing sloshing dynamics in liquid handling robotic systems has been faced by designing a dynamic filter that starting from the desired motion of the liquid container calculates the complete position/orientation trajectory for the robot end-effector. Specifically, a design philosophy mixing a filtering technique that suppresses the frequency contributions of the reference motion that may cause liquid oscillations and an active compensation of lateral accelerations by a proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The first question that arises when analyzing all the aforementioned approaches for non-prehensile transportation, especially the last one, is whether an expression of feedforward compensation can be found that does not depend on friction parameters. This doubt arises because the approach we proposed for sloshing suppression, based on tilting compensation, only requires knowledge of linear accelerations [4].An experimental application to a waiter task suggests that the same control is able to maintain an object in equilibrium on a tray even when very fast motions are applied (see the video [3]). Additionally, while many researchers agree on the application of orientation compensation to prevent slipping, the problem of determining the optimal location of the center of rotation has not been addressed yet.…”
Section: Related Work and Contribution Of The Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The first question that arises when analyzing all the aforementioned approaches for non-prehensile transportation, especially the last one, is whether an expression of feedforward compensation can be found that does not depend on friction parameters. This doubt arises because the approach we proposed for sloshing suppression, based on tilting compensation, only requires knowledge of linear accelerations [4].An experimental application to a waiter task suggests that the same control is able to maintain an object in equilibrium on a tray even when very fast motions are applied (see the video [3]). Additionally, while many researchers agree on the application of orientation compensation to prevent slipping, the problem of determining the optimal location of the center of rotation has not been addressed yet.…”
Section: Related Work and Contribution Of The Papermentioning
confidence: 99%
“…respectively, the constraint (30) for a triangular velocity trajectory becomes, in the worst case 3 ,…”
Section: A Point-to-point Trajectory For Solid Object Manipulationmentioning
confidence: 99%